Pain: a prevalent feature in patients with mucopolysaccharidosis. Results of a cross‐sectional national survey. Issue 2 (22nd July 2014) - Brands, Marion M. G.; Güngör, Deniz; den van Hout, Johanna M. P.; Karstens, Francois P. J.; Oussoren, Esmee; Plug, Iris; Boelens, Jaap Jan; van Hasselt, Peter M.; Hollak, Carla E. M.; Mulder, Margot F.; Gozalbo, Estela Rubio; Smeitink, Jan A.; et al.
Abstract: Background: While clinical observations suggest that many patients with mucopolysaccharidosis (MPS) experience chronic pain, few studies have assessed its extent and impact. We therefore investigated its prevalence in patients with all types of MPS in the Netherlands. We also examined the association between pain and health related quality of life (HRQoL) and other clinical variables. Methods: We conducted a nationwide MPS survey that used questionnaires on MPS and disease‐related symptoms (MPS‐specific questionnaire), developmental level (Vineland Screener 0–6 years), quality of life (PedsQl and SF‐36), and disability (Childhood Health Assessment Questionnaire). Depending on their age and developmental level, patients or their parents were asked to assess pain by keeping a pain diary for five consecutive days: either the Non‐communicating Children's Pain Checklist – Revised (3–18 years intellectually disabled and children <8 years), the VAS‐score (> 18 years), or the Faces Pain Scale – Revised (8–18 years). Results: Eighty‐nine MPS patients were invited, 55 of whom agreed to participate (response rate 62 %; median age 10.9 years, range 2.9–47.2 years). They covered a wide spectrum in all age groups, ranging from no pain to severe pain. Forty percent scored above the cut‐off value for pain. Most reported pain sites were the back and hips. While the MPS III group experienced the highest frequency of pain (52.9 %), 50 % of patients with an intellectual disability seemed to experience pain, versus 30 % of patients with a normal intelligence. MPS patients scored much lower (i.e., more pain) than a random sample of the Dutch population on the bodily pain domain of the SF‐36 scale and the PedsQl. Conclusion: With or without intellectual disabilities, many MPS patients experience pain. We recommend that standardized pain assessments are included in the regular follow‐up program of patients with MPS.